The 5 truths for transformational leaders : how nonprofit organizations thrive, grow, and make a profound difference - Mishrell, Ed (John Wiley & Sons, Inc., 2023)
"More than 1.4 million non-profit organizations operate in the United States. These organizations have a combined revenue of some $2.26 trillion and employ 10% of the nation's workforce. Over 60 million people serve as board members and volunteers. These organizations represent the promise and aspirations of America. Every day in communities big and small, nonprofit organizations bring people together to feed, shelter, care for, heal, inform, protect, educate, inspire, nurture, build, encourage and protect. The missions of nonprofit organizations are central to the health and prosperity of our nation. Some of these organizations are strong and thriving, but many struggle to survive. What makes the difference? Why do some nonprofit organizations prosper and grow while others struggle? The answer is leadership, but most leadership models are based on the experience of successful for-profit corporations. Nonprofits especially small nonprofits have unique leadership requirements. They require a mission focused leadership model. The Five Truths for Transformational Leaders engages professionals and board leaders on a quest to achieve extraordinary results. The five truths are based on the authors forty years of experience as a nonprofit leader and interviews with staff and board leaders of organizations that achieved unprecedented, sustained transformational growth. Each of the five truths is supported by quotes and observations from board and staff leaders of organizations that more than doubled operating revenue over five years"--